Determinação de adenosina deaminase, fator de necrose tumoral-alfa e interleucina-1 em gestantes portadoras de pré-eclâmpsia - Giorgi, Vanessa Silvestre Innocenti [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Preeclampsia is a specific disorder of pregnancy, characterized by arterial hypertension and proteinuria detected after 20 weeks of gestation. This pathology is associated with hyperuricemia, higher levels of pro-inflammatory cytokines, enhanced leukocyte activation and oxidative stress. Adenosine deaminase (ADA) is an enzyme present in all human tissues and, it is involved with the maturation of the immune system. Although its function is not fully understood, ADA is considered an indicator of cellular inflammation and, its increased serum concentration is observed in inflammatory diseases, such as tuberculosis and rheumatoid arthritis. This study aimed to assess serum ADA levels in preeclamptic patients (PE) compared with normotensive pregnant (NT) and non-pregnant women (NP), and to correlate these values with TNF-α and IL-1β production. Ninety pregnant women were included: 60 were pre-eclamptic and 30 were normotensive matched for gestational age. As control group 20 healthy non-pregnant women matched with pregnant for age were included. Peripheral blood mononuclear cells (PMMC) obtained from the three groups studied were cultured with or without lipopolysaccharide (LPS) for 18h at 37oC, and TNF-α and IL-1β production was assessed in the supernatant of cultures by enzyme immunoassay (ELISA). ADA plasmatic concentration was determined by colorimetric method. The results show that ADA plasma levels were significantly higher in PE group compared with NT and NP groups. A positive correlation between ADA and uric acid levels was detected in preeclamptic women. There was no significant difference in relation to ADA levels when PE patients were classified in early and late-onset PE. The endogenous production of IL-1β and TNF-α by PBMC was significantly higher in PE group than in NT and NP women, showing the activation state of these cells in PE. LPS induced...(Complete abstract click electronic access below)

A pré-eclâmpsia é uma síndrome específica da gravidez, caracterizada por hipertensão arterial e proteinúria, identificadas após a 20a semana de gestação. Essa patologia está associada com hiperuricemia, níveis séricos elevados de citocinas inflamatórias, ativação de leucócitos e estresse oxidativo. A adenosina deaminase (ADA) é uma enzima presente em todos os tecidos e está envolvida com a maturação de células do sistema imunológico. Apesar de suas funções não estarem completamente elucidadas, a ADA é considerada um indicador de inflamação celular e, o aumento de sua concentração no soro é observado em doenças inflamatórias, como tuberculose e artrite reumatóide. O presente projeto teve por objetivo avaliar a concentração sérica de ADA em gestantes portadoras de pré-eclâmpsia (PE) comparadas a gestantes normotensas (GN) e mulheres não-grávidas (NG) e correlacionar esses valores com a produção das citocinas inflamatórias TNF-α e IL-1. Foram avaliadas 90 gestantes, sendo 60 portadoras de pré-eclâmpsia e 30 gestantes normotensas, pareadas pela idade gestacional. Como controle foram incluídas 20 mulheres saudáveis não-grávidas pareadas com as gestantes pela faixa etária. Células mononucleares de sangue periférico (PBMC) obtidas dos três grupos foram cultivadas na ausência ou presença de lipopolissacáride (LPS) por 18h a 37oC e a produção de TNF- e IL-1  foi avaliada no sobrenadante de cultura dessas células por ensaio imunoenzimático (ELISA). A concentração plasmática de ADA foi determinada, por método colorimétrico. Os resultados mostram que os níveis de ADA foram significativamente mais elevados no plasma de gestantes com PE em comparação aos grupos GN e NG, havendo correlação positiva com os níveis de ácido úrico nas gestantes pré-eclâmpticas. Não houve diferença significativa nos níveis de ADA...(Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Mulheres grávidas; Pre-eclampsia; Adenosina